METHODS OF FORMING LANGUAGE COMPETENCE IN TEACHING RUSSIAN AS A FOREIGN LANGUAGE (ON THE MATERIAL OF STABLE PHRASES) - Dzhankhotova,; Kharayeva,; Abazova,; Gutaeva, (Revista Inclusiones, 2019)
The present paper discusses issue of teaching Russian phraseology to foreign students; it is noted that having a distinct national cultural identity, the phraseological foundation of the Russian language is a rich source of linguistic and cultural knowledge and a fruitful basis for solving important linguo-didactic tasks. This work describes the methodological techniques allowing to learn the features of phraseological units as figurative, meaningful units of the language, focusing on the fact that studying Russian phraseology contributes to the formation of communicative and cultural competencies of foreign students.